Clinical Factors Associated With Mortality Among Burn Patients: A Retrospective Observational Cohort Study - Merina Widyastuti; Natasya Aurelya Putri; Sri Anik Rustini; Sifira Kristiningrum (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: Burn injuries are a medical emergency requiring prompt treatment in the early phase to prevent complications and death. This study analyzes the relationship between hospital arrival time, inhalation injury, burn etiology, and mortality rates in burn patients. Method: This study employed an observational analytic design with a retrospective observational cohort study for the period from January 2023 to December 2025. The study population consisted of patients with burn injuries treated in the emergency department. Based on medical records, 77 patients were selected using total sampling. Data were analyzed using the chi-square test and the Mann-Whitney U test. Results: The analysis revealed a significant association between inhalation trauma and burn etiology with mortality, both at p = 0.003. Conversely, the timing of patient arrival at the emergency department did not show a statistically significant association with patient outcomes (p=0.690). Conclusions: Mortality among burn patients was significantly associated with inhalation trauma and burn etiology. Time to emergency department arrival showed no significant effect. Clinical management should prioritize early detection of inhalation injury and etiology-specific interventions to reduce mortality.